2020
DOI: 10.1155/2020/4364650
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Oxidative Stress Responses of Imidacloprid and Glyphosate in Human Prostate Epithelial WPM-Y.1 Cell Line

Abstract: Insecticide imidacloprid and herbicide glyphosate have a broad spectrum of applicable use in the agricultural sector of Egypt. Their ability to induce in vitro cytotoxic and oxidative stress on normal human cells (prostate epithelial WPM-Y.1 cell line) was evaluated with the methyl tetrazolium test (MTT) and histopathological investigation. Cell viability was evaluated with an MTT test for 24 h. The median inhibition concentration (IC50) values were 0.023 and 0.025 mM for imidacloprid and glyphosate, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…For example, glyphosate induced significant alterations to oxidative stress biomarkers in normal human prostate epithelial WPM-Y.1 cell line. 41 Similar findings were reported using mice, 42,43 and C. elegans . 44 In the current study, glyphosate did not cause an increase in the induction of oxidative DNA damage, as our results show no changes in the levels of 8-OHdG at any examined concentrations.…”
Section: Discussionsupporting
confidence: 75%
“…For example, glyphosate induced significant alterations to oxidative stress biomarkers in normal human prostate epithelial WPM-Y.1 cell line. 41 Similar findings were reported using mice, 42,43 and C. elegans . 44 In the current study, glyphosate did not cause an increase in the induction of oxidative DNA damage, as our results show no changes in the levels of 8-OHdG at any examined concentrations.…”
Section: Discussionsupporting
confidence: 75%
“…Poisoning impacts peripheral muscarinic and nicotinic receptors, as well as the central nervous system [99][100][101][102][103]. Some manifestations of a cholinergic crisis include nausea, vomiting, diarrhea, abdominal cramp, urinary incontinence, miosis, salivation, lacrimation, bronchorrhea, bradycardia, hypotension, fasciculation, muscle paralysis, dizziness, confusion, seizures, coma, and respiratory failure [8,100,102,[104][105][106]. These effects may occur immediately with exposure to pesticides [107][108][109][110].…”
Section: Acute Toxic Effectsmentioning
confidence: 99%
“…Zhang et al [81] studied the relationship between liver conditions and neurodegenerative diseases and Butyrylcholinesterase (BChE); the results indicated accurate IC 50 values for tacrine with respect to BchE (8.6 nm). Abdel-Halim et al [8] discussed the ability to induce in vitro cytotoxic and oxidative stress in normal human cells with an MTT test; the results showed that the level of inhibition concentration (IC50) values was 0.023 and 0.025 mm for imidacloprid and glyphosate, respectively. Forsythe et al [10] used bioengineered 3D human liver and cardiac organoids to screen a panel of thallium and glyphosate and discussed the response of the organoids to these compounds; the results indicated that the IC 50 of glyphosate was 13.5 µm.…”
Section: Acute Toxic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, IMI has been detected in the human body according to several studies [117][118][119] due to its extensive use that leads non-target organisms to be highly exposed to its residues. The toxicity of IMI has been linked to hepatotoxicity and nephrotoxicity, as well as neurotoxicity in several experimental models [120,121]. Moreover, IMI has also been demonstrated be very toxic in human prostate epithelial cells and able to induce apoptotic effects as well as oxidative stress [122].…”
Section: Pesticides/biocides and Plasticizersmentioning
confidence: 99%